THE DECISION OF THE ASSEMBLY TO FILE A LAWSUIT (INITIATING A DISPUTE FOR THE EXCLUSION OF A MEMBER FROM LIMITED LIABILITY COMPANY - Marjanski, Vladimir (Glasnik Advokatske komore Vojvodine, 2024)
Exclusion of a member from a limited liability company is one of the grounds for termination of membership in multi-member limited liability companies. The Serbian Companies Act distinguishes between two procedures for excluding a member from a limited liability company: 1) exclusion of a member by decision of the assembly (out-of-court exclusion) and 2) exclusion of a member by a court decision, depending on the reasons for the exclusion. The decision of the assembly to file a lawsuit (initiating a dispute) for the exclusion of a member from the company is, in Serbian law, a basic prerequisite for conducting a dispute for the exclusion of a member when the company appears as the plaintiff. Although this decision is only an initial act that creates the authority to file a lawsuit for the exclusion of a member from the company, its detailed analysis opens up a number of important questions. In connection with the assembly's decision to file a lawsuit (initiating a dispute) for the expulsion of a member from the company, several of the most significant issues are analyzed in the paper: the question of the legal character of that decision and its connection with the content of the lawsuit for the expulsion of a member, issues related to the procedure for making this decision (the question of jurisdiction, quorum, majority for making a decision, persons with the right to vote regarding the making of that decision), as well as the question of its content.
Keywords: exclusion of a member, decision of the assembly on filing a claim for exclusion, claim for exclusion of a member from the company, limited liability company